The Learning Environment and Students’ Learning Interest in Online Learning - Dahniar Ramadani; Siti Suharni Simamora (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
This study aims to investigate the relationship between the learning environment and students' interest in online classes in State Senior High School 1 of Sei Kanan in Class X-Science. This correlational study employs a qualitative descriptive approach. This study's population consisted of all 72 students, with 36 students from Class X-Science 1 and 36 students from Class X-Science 2 serving as samples. Techniques and data collecting techniques employed were questionnaires. The results obtained from the learning environment and student interest in learning were quite good, with a good learning environment that was very conducive to the success of students in learning and a clean, comfortable, fresh, and bright learning atmosphere that was sufficient to create a pleasant learning atmosphere, in addition to a high level of student interest in learning. In this instance, a good learning environment would undoubtedly facilitate the easy implementation of learning with a comfortable learning environment that will interest and engage students in learning.